Foreword - Aldred, Wendy (Victoria University of Wellington Law Review, 2014)
This article is the foreword to this special issue of the Victoria University of Wellington Law Review in honour of Harriette Vine, the Faculty's first woman law graduate. Women continue to lag behind men in terms of advancement in the legal profession, notwithstanding that for over 20 years women have comprised the majority of law graduates. 100 years after Harriette Vine's graduation, the Wellington Women Lawyers Association ('WWLA') ran an essay competition with the topic Harriet's challenges 100 years on: Same or different?, which asked entrants to outline the challenges that confront women law graduates today and discuss possible ways to overcome these.